(untitled) (Quinto Sol, 2021)
From the texts on morality and urbanity, we address the phenomenon of civic education in Chile in the context of the 19th century as a fundamental expression of the republican ideology. To do this, a cartography of the manuals of the period 1819-1900 published in the country or foreigners adapted to the Chilean idiosyncrasy is carried out. The following factors are considered: author, publisher, addressee, geographic distribution, and content, among others. The “performative” role played by urbanity in the school curriculum as a key element in the process of secularization and construction of citizenship was then analyzed. The focus was on the paradigmatic case of the Carreño Manual, due to its validity to date. In this way, the study makes a new contribution to a historiography on texts on urbanity and civic education in Chile, which contributes to laying the foundations for future comparative analyzes in Latin America on the subject.